VASCULAR COMORBIDITY: GENERAL APPROACHES TO PREVENTION AND TREATMENT - R. G. Oganov (Столичная издательская компания, 2015)
The problem of vascular comorbidity in patients with cardiovascular diseases, its effect on the cardiovascular risk, general causes and approaches to the prevention and treatment of vascular comorbidity are considered.